Establishment of Leucaena leucocephala with high sowing density under coconut (Cocus nucifera) tree - Anguiano, J. M.; Aguirre, J.; Palma, J. M. (Cuban Journal of Agricultural Science, 2012)
A study was conducted on a soil with loamy-sandy texture to assess the agronomic, physiological and productive performance of Leucaena leucocephala in high sowing density under coconut tree. A random block design was used with factorial fit. The factors analyzed were: sowing density, with three levels of 40, 60 and 80 thousand plants of leucaena/ha, and tree age, at 5, 40, 55, 70, 85 and 100 d, with three replicates. The sowing was conducted on February 2009, at depth from 2 to 3 cm. The seeds were scarified and inoculated with rhizobium and mycorrhizae. After 20 d the tree emerged, the treatments were fertilized with the formula 00-20-10-20, provided by diatom land in dosages of 700 kg/ha. The manual control of weeds in the area was conducted. In all the variables studied there was interaction effect (P < 0.001). The best values found at 100 d of age were for the treatment with 80 thousand plants of leucaena/ha in stem diameter (1.27 cm), dry weight of leaves (49.54 g), dry weight of plant (72.61 g), biomass production (6159 kg/ha), productive rate (61.59 kg DM/d/ha) and water use efficiency (6.84 kg DM/m3). These numbers were statistically similar to those obtained with 60 thousand plants of leucaena/ha, for plant height (133.67 and 138.28 cm) and number of leaves (23.94 and 24.72). The sowing of 80 thousand plants of leucaena/ha associated with coconut tree, as high density system, could be proposed as alternative for intensifying the agrosilvopastoral systems in the tropical area. Key words: leucaena, multiestratum, intensification, biomasa, grazing.